Metaliteracy in practice - Jacobson, Trudi E. 1957-; Mackey, Thomas P. (Facet Publishing, 2016)
In their earlier book Metaliteracy, the authors offered an original framework for engaging learners as reflective and collaborative participants in today's complex information environments. Now, they move that comprehensive structure for information literacy firmly into real-world practice, highlighting the groundbreaking work of librarians and faculty who are already applying the metaliteracy model in distinctive teaching and learning settings. Representing multiple disciplines from a range of educational institutions, this book explores relationships among metaliteracy, digital literacy, and multimodal literacy; incorporating the ACRL Framework for Information Literacy for Higher Education; the metaliteracy model and emerging technologies; flexible course design and social media; students as creators of information; application of metaliteracy in specialized environments, such as nursing education; metaliteracy and institutional repositories; LibGuides as a student information creation tool; the metacognitive dimension of research-based learning; metaliteracy as empowerment in undergraduate learning outcomes; agency and the metaliterate learner; and metaliteracy, agency, and praxis. The case studies presented in this valuable resource demonstrate how librarians and educators can help students effectively communicate, create, and share information in today’s participatory digital environments.--Provided by publisher.